Conceptual model of volatility index for Islamic Real Estate Investment Trusts (I-REITs) / Mohd Fariz Helmi Husain and Muhammad Najib Razali - Husain, Mohd Fariz Helmi; Razali, Muhammad Najib (2021)
This study will present the conceptual model of volatility index of the Islamic REITs (IREITs which covers I-REITs in Malaysia. This is aimed to provide clear evident and perception for I-REITs as major investment option in property security market. The volatility index will be considering the major indicators of performance in portfolios' assets performance namely Sharpe Index, potential of diversification, portfolio optimisation, causality, volatility and spillovers. Research on Global I-REITs have not been significant yet. This is especially on the issue of volatility index due to the high integration of major portfolios assets market in recent years. This study attempts to fill the space in the picture of I-REITs markets by using a volatility technique. Islamic REITs has attracted other countries to start diversifying their businesses as well as optimizing their countries' investment opportunities.